Transformation Geometry in Toraja Carving - Beatric Videlia Remme' (Universitas Negeri Makassar, 2020)
Toraja carving (passura ') is the result of Toraja culture which is preserved and contains various values of life. In additon, Toraja carving is also rich in mathematical concepts, particularly geometric shapes. This study aims to identify the transformational geometry concepts found in Toraja carving. This research is qualitative research with an ethnographic approach and is conducted in 3 stages. Informants (data sources) in this study are people who understand the ins and outs of Toraja culture. The data in this study were obtained from data from interviews with informants, field notes made during the study, and documentation results in the form of photos of engraving and carving time. To obtain valid data, researchers used theoretical triangulation. The results of the study show that in the tongkonan and lumbung Toraja carvings there are concepts of transformation geometry, namely reflections both on the x-axis, y-axis, y = x, y = -x, and towards point 0 (0,0), translation, rotation, and dilation.